Priming of NK Cell Anti-Viral Effector Mechanisms by Direct Recognition of Human Cytomegalovirus - Muntasell, Aura; Costa-Garcia, Marcel; Vera, Andrea; Marina-Garcia, Noemi; Kirschning, Carsten J.; López-Botet, Miguel (Frontiers in Immunology, 2013)
NK cells play an important role in the defense against viral infections. Activation of resting NK cells is tightly controlled by the balance of surface inhibitory and activating receptors and aided by cytokines released by accessory cells along the anti-viral response. On the other hand, NK cells express functional pattern recognition receptors (PRRs) whose function has been mostly addressed by the use of synthetic agonists. The present study was undertaken to investigate whether NK cells could directly recognize a complex pathogen such as Human Cytomegalovirus (HCMV). Exposure of primary human NK cells to HCMV (TB40/E strain) induced the expression of CD69, promoted IFNγ secretion, and increased their cytotoxic activity against HCMV-infected autologous monocyte-derived dendritic cells. The divergent response induced by infective and UV-inactivated virions indicated the involvement of different NK cell sensors in the recognition of HCMV. The fact that NK cell activation could be partially prevented by blocking mAb specific for IFNAR and TLR2, together with the induction of IFNβ mRNA, supported the involvement of IFNβ and TLR2 in the response to HCMV. Thus, our data indicate that simultaneous activation of several PRRs leads to the autonomous priming of NK cell effector functions and could be a previously unappreciated mechanism presumably contributing to the control of HCMV infection.